2011
DOI: 10.1590/s0102-76382011000200010
|View full text |Cite
|
Sign up to set email alerts
|

Os perfusionistas Brasileiros e o ajuste do rolete arterial: comparação entre a calibração estática e dinâmica

Abstract: Results: There were 56 perfusionists in this study. Pressure average of 56 measurements of dynamic calibration was 434 ± 214 mmHg; 76% of measurements were within the recommended range for the use of the dynamic calibration method (between 150 and 500 mmHg).Conclusion: Brazilians perfusionists tend to adjust roller pumps with less occlusive settings. The amplitudes of the dynamic calibration pressure tend to be smaller for more experienced perfusionists because their skills increase with 206VIEIRA JUNIOR, FU E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…With roller pumps, cell trauma may occur when the rollers are poorly calibrated or set. In centrifugal pumps, hemolysis may occur when there is excessive negative pressure driving blood flow [ 22 ] . Pohlmann et al [ 23 ] reported that suction during CPB is a major factor in CPBassociated hemolysis, and that the negative pressure exerted by the pump and exposure of blood to air combine to make this hemolysis more severe.…”
Section: Discussionmentioning
confidence: 99%
“…With roller pumps, cell trauma may occur when the rollers are poorly calibrated or set. In centrifugal pumps, hemolysis may occur when there is excessive negative pressure driving blood flow [ 22 ] . Pohlmann et al [ 23 ] reported that suction during CPB is a major factor in CPBassociated hemolysis, and that the negative pressure exerted by the pump and exposure of blood to air combine to make this hemolysis more severe.…”
Section: Discussionmentioning
confidence: 99%